Perbedaan Kadar Tumor Marker CEA dan CA 125 Antara Karsinoma Paru dengan Metastase Tulang dan Karsinoma Paru Tanpa Metastase Tulang di RSUP Sanglah Denpasar - Tamzil, Kezia Aurelia; Wiratnaya, I Gede Eka; Astawa, Putu; Suyasa, I Ketut (Universitas Udayana, 2022)
Lung carcinoma is one of the most common malignancies metastasized to bone, as much as 30-40% of lung malignancies metastasize to bone in the course of the disease. Carcinoembryonic Antigen (CEA) and Cancer Antigen 125 (CA 125) are tumor markers often used to assess lung malignancy. Eventhough the character of tumor markers are less sensitive and specific, some evidence address an increase in these tumor markers in the case of lung malignancies which metastasize to bone. The purpose of this study is to prove an increase in the levels of tumor markers CEA and CA 125 in lung carcinoma with bone metastases compare to lung carcinoma without bone metastases. A cross sectional study consecutively by reviewing lung carcinoma with bone metastases and without bone metastases in patient’s medical record between 2013-2021 at RSUP Sanglah Denpasar. Of 50 lung carcinoma patients (25 patients with bone metastases and 25 patients without bone metastases), levels CEA and CA 125 tumor markers were processed using SPSS. The results showed levels of CEA were significantly higher in lung carcinoma with bone metastases (p=0,028), but levels of CA 125 were not significantly higher in lung carcinoma with bone metastases (p=0,796). The results of the study concluded that levels of CEA could be used as a valuable marker to assess lung malignancy which metastasized to bone in clinical application. Keywords: Tumor Marker Levels, CEA, CA 125, Lung Carcinoma, Bone Metastases